Te Pā Harakeke: Māori and non-Māori parent (whānau) support of culturally responsive teaching pedagogies - Highfield, Camilla; Webber, Melinda; Rachel Woods (The Australian Journal of Indigenous Education, 2023)
This strengths-based paper draws on the qualitative and quantitative survey results from whānau (family members) of tamariki (children) attending 12 schools in an urban area in New Zealand with a high proportion of Māori people. The paper describes the positive impact of effective family engagement on tamariki, from the perspectives of whānau, paying particular interest to the differences between Māori and non-Māori whānau. The views of all whānau who participated in the project support the importance of relational and culturally sustaining aspects of teaching, and challenge commonly held stereotypes about indigenous parents’ low expectations in relation to their children’s education. The paper amplifies whānau voice about their children’s school enjoyment, perceptions of teacher support and future career aspirations for their tamariki.